Bipolar resistive switching behavior in Ti/MnO2/Pt structure for nonvolatile memory devices - Yang, Min Kyu; Park, Jae-Wan; Ko, Tae Kuk; Lee, Jeon-Kook (AMER INST PHYSICS, 2009)
This study examined the electrical properties of Ti/MnO2/Pt devices with stable and reproducible bipolar resistive switching behavior. The dependency of the memory behavior on the cell area and operating temperature suggest that the conducting mechanism in the low resistance states is due to the locally conducting filaments formed. X-ray photoelectron spectroscopy showed that nonlattice oxygen ions form at the MnO2 surface. The mechanism of resistance switching in the system examined involves the generation and recovery of oxygen vacancies with the nonlattice oxygen ions.
Keywords: FILMS; THIN